1998
DOI: 10.2535/ofaj1936.74.6_231
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Substance P-and CGRP-immunoreactive Central Endings of the Primary Afferent Neurons to GABAergic Interneurons in the Guinea Pig Substantia Gelatinosa

Abstract: Summary: The synaptic relationships between primary afferent central endings containing substance P (SP) and calcitonin gene-related peptide (CGRP) and GABAergic internenrons in the guinea pig substantia gelatinosa of the lumbar spinal dorsal horn were studied. The pre-embedding PAP method was used for detection of GABA and the post-embedding double immunogold labeling method for SP and CGRP detection. Immunogold particles specific for SP and CGRP were mainly localized separately or together in large synaptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The granular structures are reminiscent of intracellular stores such as endoplasmic reticulum or Golgi apparatus. Neuropeptides such as CGRP are thought to be stored in, transported by and released from large vesicles with or without dense cores (42)(43)(44)(45). Thus, an alternative explanation for the increase in numbers of immunoreactive neurons may be an opening of these intracellular stores caused by infusion of the NO donor, so that more neurons gain sufficient immunoreactivity to be detected by immunofluorescence.…”
Section: Alternative Regulation Of Cgrp and Nnos Immunoreactivitymentioning
confidence: 99%
“…The granular structures are reminiscent of intracellular stores such as endoplasmic reticulum or Golgi apparatus. Neuropeptides such as CGRP are thought to be stored in, transported by and released from large vesicles with or without dense cores (42)(43)(44)(45). Thus, an alternative explanation for the increase in numbers of immunoreactive neurons may be an opening of these intracellular stores caused by infusion of the NO donor, so that more neurons gain sufficient immunoreactivity to be detected by immunofluorescence.…”
Section: Alternative Regulation Of Cgrp and Nnos Immunoreactivitymentioning
confidence: 99%
“…Particularly important is the gating of afferent input to the spinal cord. While data from rodent models also suggest that post-synaptic inhibitory circuitry in the spinal cord dorsal horn is likely to be important for regulation of nociceptive threshold, particularly in the presence of injury, available electrophysiological, pharmacological and morphological data suggest that pre-synaptic inhibition of afferent input is the dominant mechanism for inhibition of somatosensory input into the CNS (Eccles et al, 1962, Eccles et al, 1963, Nishi et al, 1974, Mokha et al, 1983, Hiura et al, 1998, Reeve et al, 1998, Rudomin and Schmidt, 1999, Bae et al, 2000, Olave et al, 2002, Sutherland et al, 2002, Sokal and Chapman, 2003, Vesselkin et al, 2003, Weng and Dougherty, 2005). Virtually all dorsal root ganglion (DRG) neurons from rat respond to GABA with a rapidly activating, bicuculline-sensitive anion current (Oyelese et al, 1995, Zhu et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most characteristic features of these terminals is the coexistence of small densely packed vesicles and variable number of large dense-core vesicles (DiFiglia et al, 1982;Carlton et al, 1987;Alvarez et al, 1993;Hiura et al, 1998). It has been shown that these axons form synaptic contacts mainly on dendrites, but axosomatic arrangements also appear frequently both in lamina I and II (DiFiglia et al, 1982;Carlton et al, 1987;Hayes & Carlton, 1992;Alvarez et al, 1993;Ribeiro-da-Silva, 1995;Hiura et al, 1998).…”
Section: Synaptic Arrangementsmentioning
confidence: 97%